The 26° Conference of the parties to the United Nations framework Convention on Climate Change: Analysis and perspective - Pinto-Bazurco Barandiarán, Jose Felix (2021)
This article will provide a brief summary of the results of the Glasgow Climate Pact and the 26th Conference of the Parties to the United Nations Framework Convention on Climate Change, what was resolved, what was not resolved, and an analysis, including their relevance for Peru.